Peningkatan Proses dan Hasil Belajar Matematika Menggunakan Model Pembelajaran Snowball Throwing Berbantu Kokami di Sekolah Dasar - Yolanda Lupita Sary (INNOVATIVE SCIENCE AND TECHNOLOGY LEARNING JOURNAL, 2026)
This study aimed to enhance the process and outcomes of mathematics learning using the Snowball Throwing model assisted by Kokami media for third-grade students at SD Negeri 101/II Muara Bungo. The research applied Classroom Action Research (CAR) with Kemmis and Taggart’s design during the second semester of the 2023-2024 academic year. Data collection included tests, observations, and documentation. Results indicated improvements in learning processes, with teacher observation scores rising from 66 in Cycle I to 99 in Cycle II. Student learning outcomes improved from 67.6% in Cycle I to 79.4% in Cycle II. In conclusion, the Snowball Throwing model assisted by Kokami effectively enhanced mathematics learning processes and outcomes.